Renal renin-angiotensin system activation in acute heart failure and its association with endothelial dysfunction, inflammation and oxidative stress. - Álvaro Alexandre Ferreira Duarte (2021)
Introduction and objectives: Acute heart failure (AHF) and cardiogenic shock (CS) are associated with high hospitalization and mortality rates. Renin-angiotensin-aldosterone system (RAAS) activation and redox dysfunction contribute to cardiac and renal dysfunction, but their interplay in human AHF and CS has not been explored. We aimed to investigate plasma and urinary angiotensinogen (P-AGT; U-AGT, an intrarenal RAAS marker) and urinary H2O2 (U-H2O2) in AHF and CS patients. Furthermore, we evaluated the correlations between them, as well as their association with endothelial dysfunction, inflammation, oxidative stress and cardiac and renal impairment. Methods: Patients with AHF (n=23) or CS (n=25) and healthy controls (n=22) were included. U-AGT, P-AGT, U-H2O2, endothelial dysfunction, inflammation, oxidative stress and cardiac/renal impairment markers were evaluated at days 1-2 (admission), days 3-4 and days 5-8 in AHF and CS patients and at a single time point in controls. Results: At admission, AHF and CS patients had similar P-AGT, higher U-AGT and lower U-H2O2 than controls. There were no changes in P-AGT, U-AGT or U-H2O2 along hospitalization. P-AGT and U-AGT positively correlated with endothelial dysfunction, inflammation and oxidative stress, while U-H2O2 negatively correlated with these biomarkers and with U-AGT in the overall study population. Among patients, U-H2O2 positively correlated with inflammation, oxidative stress and P-AGT, and both U-AGT and U-H2O2 were associated with renal impairment. Conclusions: AHF and CS patients appear to have intrarenal RAAS activation and increased H2O2 consumption, probably by myeloperoxidase. Furthermore, their association with renal dysfunction is likely related to endothelial injury, inflammation and oxidative stress.